Medications influencing central cholinergic neurotransmission affect saccadic and smooth pursuit eye movements in healthy young adults - Naicker, Preshanta; Anoopkumar-Dukie, Shailendra; Grant, Gary D.; Kavanagh, Justin J. (Psychopharmacology, 2017)
Rationale Acetylcholine is an important neuromodulator in the central nervous system, where it plays a significant role in central functions such as the regulation of movement. Objective This study investigated the pharmacological effects of over-the-counter anticholinergic medications on saccadic and smooth pursuit eye movements, in order to establish the significance of central cholinergic pathways in the control of these centrally regulated oculomotor processes. Methods Sixteen subjects (mean age 23 ± 3 years, 9 females) performed pro-saccadic, anti-saccadic and smooth pursuit eye movement tests, while an eye tracker collected eye movement data. Oculomotor assessments were performed pre-ingestion, 0.5 and 2 h post-ingestion of drugs with varying degrees of central anticholinergic properties. The drugs tested were promethazine, hyoscine hydrobromide, hyoscine butylbromide and placebo. Results The drug intervention with stronger central anticholinergic properties, promethazine, decreased amplitude and increased velocity in the pro-saccadic task and increased duration in the anti-saccadic task. Promethazine, once again, was the only drug to decrease eye velocity in the smooth pursuit test. Conclusion The prominent effects of the stronger central anticholinergic promethazine, on saccadic and smooth pursuit eye movements, potentially conveys the significance of central cholinergic pathways in the control of these centrally regulated oculomotor processes.